Deca‐band structure reutilization MIMO antenna for 4G/5G full‐screen metal frame smartphone operation. Issue 12 (21st September 2021) - Fang, Yixiang; Liu, Ying; Jia, Yongtao; Liang, Junjie
Abstract: This article presents a deca‐band multi‐input multi‐output (MIMO) antenna for full‐screen metal frame smartphone, which covers wideband of GSM850, GSM900, DCS, PCS, UMTS, LTE2300, LTE2500, WLAN/WiMAX, N78, and sub‐6 GHz (4.8–5.1 GHz) bands table. Two kinds of antenna structures are positioned on the long side edge and form two 2 × 2 MIMO array, covering the low‐band (824–960 MHz) and mid‐band (1710–2690 MHz/3300–3800 MHz), respectively. Four slot antennas are distributed on both sides of the short side edge. Each slot is connected to an antenna structure on the long side edge, sharing one port to form the high‐band structure. By reutilization the low and mid‐band structures, the high‐band structure can achieved a wide band bandwidth without any additional matching structures. The high‐band structure is composed of 4 × 4 MIMO array and covers the band of 4800–5825 MHz. A prototype of the proposed MIMO antenna is fabricated and measured. The isolation of the antenna is larger than 15 dB, the efficiencies are between 31% and 63%, and the ECCs is less than 0.3, which shows that the proposed antenna has great potential in the future 4G/5G smartphone application.